2017
DOI: 10.1130/ges01500.1
|View full text |Cite
|
Sign up to set email alerts
|

Lineament domain analysis to infer groundwater flow paths: Clues from the Pale di San Martino fractured aquifer, Eastern Italian Alps

Abstract: An automatic lineament extraction was carried out on a processed digi tal elevation model of a highaltitude Alpine fractured reservoir, the Pale di San Martino area (Dolomites) located in the southern sector of the Eastern Italian Alps. The strike of the main lineament domain indicates the direction of the principal crustal stress. This direction was compared with earthquake focal mechanisms to confirm the orientation of the regional crustal stress. The two data sets provide similar results and show a NNWSSE m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…They are spatially distributed within a well‐defined area affected by tectonic stress and cluster around preferential orientations to form lineament domains that are parallel to the maximum horizontal stress ( Sh max ) and perpendicular to the minimum horizontal stress ( Sh min ) (Pinheiro et al., 2019; Wise et al., 1985). In this way, lineament domains can be used to infer the crustal stresses and kinematics of the upper crust at regional scale (Cianfarra & Salvini, 2014, 2016b; Lucianetti et al., 2017; Pinheiro et al., 2019; Wise, 1982; Wise et al., 1985).…”
Section: Structural Analyses and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are spatially distributed within a well‐defined area affected by tectonic stress and cluster around preferential orientations to form lineament domains that are parallel to the maximum horizontal stress ( Sh max ) and perpendicular to the minimum horizontal stress ( Sh min ) (Pinheiro et al., 2019; Wise et al., 1985). In this way, lineament domains can be used to infer the crustal stresses and kinematics of the upper crust at regional scale (Cianfarra & Salvini, 2014, 2016b; Lucianetti et al., 2017; Pinheiro et al., 2019; Wise, 1982; Wise et al., 1985).…”
Section: Structural Analyses and Resultsmentioning
confidence: 99%
“…Azimuthal analyses were performed by means of spatial polymodal Gaussian best fit techniques that enabled identification of independent azimuthal groups both in the mapped structures (Sections 3.1 and 3.2) and lineaments (Section 3.3) and were automatically identified in the SPT (e.g., Cianfarra & Salvini, 2014, 2015Lucianetti et al, 2017;Pinheiro et al, 2019;Rossi et al, 2018;Wise et al, 1985). Spatial frequencies were investigated to infer the periodicity of the structures related to tectonic conditions.…”
Section: Structural Analyses and Resultsmentioning
confidence: 99%
“…Lucianetti et al [48]; and Rossi et al [49]), and according to the geodynamic meaning of lineament domains, the maximum horizontal stress component (Shmax) and the minimum horizontal stress component (Shmin) in the upper/brittle crust are, respectively, parallel and perpendicular to the principal lineament domain. Thus, the performed lineament domain analysis suggests that the Shmax in the study region is ENE-WSW trending, and the Shmin is NNW-SSE oriented.…”
Section: Results: Data Analyses 41 Lineament Domain Analysismentioning
confidence: 99%
“…The structural lineaments outcropping in part of southeast Brazil (specifically the Atlantic Plateau) were automatically detected and mapped in order to identify the main tectonic trends. According to Wise et al [45], Cianfarra and Salvini [46,47], Lucianetti et al [48], and Rossi et al [49], lineaments cluster in azimuthal families called domains, which have a relationship with the upper crustal stress field. In the present study, the lineaments were identified on the Digital Elevation Model (DEM) of the Shuttle Radar Topography Mission (SRTM) data, whose spatial resolution is 30 m (1 arcsecond) in the investigated area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation